THE ANALYSIS OF TEACHING STRATEGIES IN READING COMPREHENSION - Rabiatul Adawiah; Konder Manurung (Tadulako University, 2021)
This study is to investigate the strategies mostly applied by teachers in teaching reading comprehension in scientific writing/journal articles. This research formulate from library research used scientific writing (journal articles) 2010 – 2021 and how is the implementation of the teaching strategies in reading comprehension the most frequently used on journal articles. This study used qualitative research design. The data were collected by library research the documentation. The data was collected from journal articles that related with the topic. To collected data is used five steps: 1) Searching valid data and resources relevant with the topic, 2) Finding the key information from the data, 3) Taking notes from the essentials information, 4) Organizing the described data into their classifications, 5) Choosing the topic to be analyzed. Based on the findings from ten journal articles, the researchers concludes that the teaching strategies QARs, Scaffolding, Memorizing strategy, Discussion strategy, Reading Aloud, Question generating, Encouraging the use dictionary, Evaluating comprehension in particular task, Brainstorming and Understanding text .From the ten teaching strategies in reading comprehension researcher found the most frequently strategies used in teaching reading comprehension namely, Question-Answer relationships (80%). In accordance with the statement of Adler (2003) QARs is the effective strategy were used in teaching reading comprehension. Teaching strategies has different ways of learning but has the same goals, which is to help students in understanding reading difficulties.